Pendekatan Psikologis dalam Pendidikan Inklusif: Studi tentang Strategi Guru Menangani Anak Berkebutuhan Khusus - Patikan, Krisnawati; Windarti, Maria Titik (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2026)
This study aims to examine the application of psychological approaches by teachers in inclusive learning at Gamaliel Christian Kindergarten in Palu. The study uses a qualitative method with a focus on teachers' strategies in assisting children, especially children with special needs. The results of the study show that teachers have made efforts to understand the emotional and social conditions and developmental characteristics of children through a personal approach, play-based learning methods, the use of simple learning media, and the provision of positive reinforcement. These strategies help to create a safe, comfortable, and inclusive learning environment for all students. However, the implementation of psychological approaches has not been optimal due to limitations in teachers' competencies in inclusive education, a lack of specialized training, the unavailability of professional assistants, and limitations in supporting facilities and infrastructure. These conditions have resulted in individual assistance for children with special needs not being carried out to the fullest extent possible.